Immunoselection techniques in hematopoietic stem cell transplantation. Issue 3 (June 2016) - Li Pira, Giuseppina; Biagini, Simone; Cicchetti, Elisabetta; Merli, Pietro; Brescia, Letizia Pomponia; Milano, Giuseppe Maria; Montanari, Mauro
Abstract: Hematopoietic Stem Cells Transplantation (HSCT) is an effective treatment for hematological and non-hematological diseases. The main challenge in autologous HSCT is purging of malignant cells to prevent relapse. In allogeneic HSCT graft-versus-host disease (GvHD) and opportunistic infections are frequent complications. Two types of graft manipulation have been introduced: the first one in the autologous context aimed at separating malignant cells from hematopoietic stem cells (HSC), and the second one in allogeneic HSCT aimed at reducing the incidence of GvHD and at accelerating immune reconstitution. Here we describe the manipulations used for cell purging in autologous HSCT or for T Cell Depletion (TCD) and T cell selection in allogeneic HSCT. More complex manipulations, requiring a Good Manufacturing Practice (GMP) facility, are briefly mentioned.